(untitled) (Asian Journal of Agriculture, 2025)
Abstract. Sabit FA, Abdullah MA, Elhadeeti SAK. 2025. Study of the contact effect of stearic acid on Trogoderma granarium Everts, 1898 (Coleoptera: Dermestidae) in the laboratory. Asian J Agric 9: 185-190. The hairy grain beetle, Trogoderma granarium Everts, 1898 is a hazardous pest that infests grains and causes great losses in the stores. Stearic acid is a suitable alternative to synthetic insecticides and a safe option to prevent infestation. The current experiment was conducted to investigate the effects of stearic acid on the adult, larval, pupal, and egg stages of T. granarium, through the direct treatment of stearic acid on beetle adults, larvae, pupal and eggs stages at exposure times of 5, 10, and 15 hours and concentrations of 20, 40, 60, and 80 ppm. Adult mortality rates varied, with the lowest value at 20 ppm concentration and exposure time of 5 hours being 46.66%, and the highest mortality (100.00%) was at 80 ppm and 15 hours. Larvae mortality rates varied between concentrations, with the highest rates at 80 ppm and 15 hours of exposure time, which reached 93.33%, and the lowest was 26.66% at 5 ppm and 5 hours. The lowest mortality rate of the pupal stage was 14.45% at 20 ppm concentration and 5 hours (exposure time), while the best results were 80.00% at 80 ppm concentration and 15 hours (exposure time). The finding showed that the optimal concentration for controlling T. granarium, the egg was 80 ppm stearic acid and an (exposure time) of 15 hours, resulting in the most significant egg damage of 61.54%. The study concluded that stearic acid has a positive lethal impact on T. granarium in different stages.